3(8-3)6-1=p

Simple and best practice solution for 3(8-3)6-1=p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(8-3)6-1=p equation:


Simplifying
3(8 + -3) * 6 + -1 = p

Combine like terms: 8 + -3 = 5
3(5) * 6 + -1 = p

Multiply 3 * 5
15 * 6 + -1 = p

Multiply 15 * 6
90 + -1 = p

Combine like terms: 90 + -1 = 89
89 = p

Solving
89 = p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
89 + -1p = p + -1p

Combine like terms: p + -1p = 0
89 + -1p = 0

Add '-89' to each side of the equation.
89 + -89 + -1p = 0 + -89

Combine like terms: 89 + -89 = 0
0 + -1p = 0 + -89
-1p = 0 + -89

Combine like terms: 0 + -89 = -89
-1p = -89

Divide each side by '-1'.
p = 89

Simplifying
p = 89

See similar equations:

| 16+t=-9 | | 13-4*n=11+2*n | | (3*5-5)(5-1)=x | | 4p-5=18 | | -7b-5(b-4)= | | x^2-7x-7=0 | | x^2+10x+39=-3x+3 | | 3x^3-17x^2=6x | | 14n-3(nt-4)= | | x^2-3x+5=9 | | 2b^2-16b=0 | | 3x-5+x=31 | | (x^2+3x+9)(2x^3+3x-4)(4x^2+2x^2-8x)= | | 8(6x+3)+3x=x | | 3x+18=x+2 | | 25*2.3=0 | | 25*2.3= | | P(x)=x^3-7x^2+17x-15 | | 4+(7*25)20-38=x | | 25*2.3=57.5 | | 4x^2+11x+5=-4x+2 | | 3x+18=x+3 | | 13a-6(a+5)=x | | 3x^3+4-2x^4= | | 82-3*8=x | | 4x^2-27x+37=-3x+2 | | 82-3*(5-3)3=x | | (7b-3)+(b-4)=646 | | y^2+10Y+25=121 | | a^2+14a-18=0 | | -12(x-4)=-138 | | z^2+12z-25=0 |

Equations solver categories